ChemInform Abstract: An Efficient Synthesis of Novel 3‐Hydroxy‐12‐arylbenzo[a]xanthen‐11‐ones and 5, 12‐Diarylxantheno[2, 1‐a]xanthene‐4, 12‐diones Using pTSA in [bmim]BF4. Issue 2 (14th January 2014) - Yadav, Sneha; Nand, Bhaskara; Khurana, Jitender M.
Abstract Simple, efficient and environmentally benign syntheses of novel xanthene derivatives via one‐pot multicomponent condensation reactions are developed.